Industrial communication networking: an ethernet based implementation - Hashim, Hairulazwan (2007)
Recent advancements achieved in industrial communications and networking technology have made it possible to apply Ethernet-based communication networking system at all levels of industrial automation, especially at the controller level where the capacity to do data exchanges in real-time is mandatory. This paper describes the development of an industrial communications network based on the Ethernet protocol and its implementation in a Computer Integrated Manufacturing (CIM) system. The application of Ethernet protocol in such a system is aimed at overcoming the difficulties experienced when trying to communicate in real-time using serial communication networks, such as when attempting to access and retrieve data from other stations. Other advantages of this approach include the relative ease of achieving system integration and the possibility of simple upgrading to include the management and enterprise levels in the industrial automation system pyramid. In this work, the Ethernet module is installed onto a supervisory PLC to integrate all the stations present in the existing CIM system found in our laboratory. The workability of this approach is analyzed and compared with the conventional serial communication network.